"I Wish I Could Have Helped Him in Some Way or Put the Family on Notice": an Exploration of Teachers' Perceived Strengths and Deficits in Overall Knowledge of Suicide. Issue 3 (3rd April 2021) - de Oliveira, Janaina Minelli; Calderón, Paloma Vicens; Caballero, Pablo Buenestado
Abstract: This article examined teachers' capacity to identify suicide myths and explored their perceived strengths and deficits in overall knowledge of suicide. One hundred twenty-nine teachers from 41 schools in Spain participated. Teachers showed moderately low suicide myth identification, holding misconceptions related to suicide verbalizations. They felt poorly informed, but acknowledged their strategic role and wanted relevant information. Training initiatives should address communicative abilities, apart from information on suicide risk factors and protective factors associated with youth, warning signs of imminent risk of suicide and basic guidelines for first intervention in students' suicide ideation, plan, or attempt.